Gender Phenomenology: Interaction and Parenting Style for Early Children In The Family - Ari Putra; Ihat Hatimah; Uyu Wahyudin; Iip Saripah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Communication and interaction dynamics are fundamental to creating harmony in the family. This study investigates interaction and communication patterns in the family environment in the rural area of Bengkulu. This research uses a qualitative methods with phenomenology approach. Phenomenological studies use Husserl's theory where what is depicted is the reality of events in the field The research results show differences in interaction and parenting patterns within the family, primarily related to the role of the husband and the dominance of communication between the mother and the child. The following finding is that parenting styles that tend to pamper children or encourage children to be independent result in limited access to gender equality within the family. These findings can trigger various debates, ranging from relevance to social and cultural change, the influence of other factors in shaping children's gender roles, the need for policy interventions, to considerations related to the generalizability of the findings, gender theory, informal education, and cultural change in the context of role research. gender and parenting. This research implies that informal education needs to be transformed to support increasing parental capacity to increase gender-responsive parenting competencies.